Minimum Time Dose in Nature to Positively Impact the Mental Health of College-Aged Students, and How to Measure It: A Scoping Review - Meredith, Genevive R.; Rakow, Donald A.; Eldermire, Erin R. B.; Madsen, Cecelia G.; Shelley, Steven P.; Sachs, Naomi A. (Frontiers in Psychology, 2020)
Background: College and university students exhibit high levels of stress, anxiety, and other mental health issues. While counseling and medications are appropriate treatments, evidence has demonstrated that spending time in nature can provide tangible benefits for mental health and well-being. This study aimed to define a ‘dose’ of time in nature that could be 'prescribed' to college-age students, as a preventative and supportive mental health intervention. The specific objectives were to: define the minimum amount of time in nature that results in positive impacts on mental health and well-being for college-aged students; describe the types of engagement with nature that elicited the impacts; and explore the most commonly used measures of effect. Methods: The scoping review was conducted following the PRISMA-ScR Checklist. A review protocol was developed. Fourteen bibliographic databases were searched and all results were blindly screened using established criteria. All titles and abstracts were screened by at least two reviewers. Studies were included if: subjects were of average college age; they examined a treatment of time (hours/minutes) in nature; they examined change in measures of mental health and well-being pre- and post-exposure; they compared participants across at least two environments; the study was published in English or French and since 1997. Results: 11,799 titles were identified and once de-duplicated, 10,917 titles were screened. 155 papers were given full text reviews, of which 14 studies were included in this review. In summary, 13 of 14 papers explicitly noted that the participants were college students. 10 of the studies took place in Japan, with others in Sweden (n=1) and the US (n=3). Results show that as little as 10 minutes of sitting or walking in diverse natural settings significantly and positively impacted defined psychological and physiological markers of mental well-being for college-aged individuals. 22 different measures were used to assess the effects of nature on mental health and well-being. Conclusions: This review provides time-dose and activity-type evidence for programs looking to use time in nature as a preventative measure for stress and mental health strain, and also demonstrates opportunities in six specific foci for more research in this area.